KEPUTUSAN INVESTASI DAN NILAI PERUSAHAAN - FAUZIAH SRI MUMPUNI; DEWI KURNIA INDRASTUTI (E-Jurnal Akuntansi TSM, 2021)
The purpose of this research is to analyze the factors that affect firm value. That factors include board size, institutional ownership, audit committee, firm size, firm age, profitability, leverage, liquidity, and investment decision. The amount of research samples are 198 data selected as final sample which are companies listed in manufacturing sector in Indonesia Stock Exchange during 2014-2016. These companies have been selected by using purposive sampling method. This research uses multiple regression analysis to investigate relation between each independent variable to firm value. The result shows that firm size, profitability, and investment decision have significant effect to firm value, while other independent variables such as board size, institutional ownership, audit committee, firm age, leverage, and liquidity do not have any effect to firm value in the manufaturing companies.